The research of the outdoor pavement colour and the solar reflection amount influence. (November 2015) - Lin, C.-B.; Lee, S.-H.; Lin, Y.-H.
Abstract : Low reflection rate material used on public pavement is the main reason for the deterioration of the environment. A great amount of energy is stored in the material, and that is being released into the atmosphere causing heat island effect. With the development of urban dwellings and the increase in living standards, people tend to do more outdoor activities than indoor, especially where the outdoor environment is paved with a hard surface. If the use of low reflection rate material could be improved, it would lower the impact on the environment.